Numerical analysis of the state of stress and strain in the Yenisei Ridge based on the regional tectonic state in the Asian continent - Akhmetov Ayan; Igor Yu. Smolin; Aleksey Yu. Peryshkin (Fracture and Structural Integrity)
The paper presents the calculation of modern tectonic flow fields in the Yenisei Ridge located on the stable Siberian Craton. At the first stage, we solve the problem of calculating the average field of tectonic flows due to collisional processes at the southern and northeastern margins of the Eurasian Plate with Indian and Arabian and with North American plates, respectively. These calculations clarify the state of stress and the structure of tectonic flows on the territory of the Siberian Craton. The subtraction of the average displacements of the Siberian Craton as a whole in the northeast direction reveals the detailed structure of tectonic flows. Structural models are built along the Batolit-1982 and Shpat geological profiles crossing the Yenisei Ridge. At the second stage, we numerically study the state of stress and strain along these profiles determined by the global tectonics of Central and Southeast Asia, as well as their structural organization and interaction with the neighboring crustal elements.